Debt : the first 5,000 years - Graeber, David, 1961-2020 (Brooklyn (N.Y.) : Melville House, 2011)
Every economics textbook says the same thing: Money was invented to replace onerous and complicated barter system--to relieve ancient people from having to haul their goods to market. The problem with this version of history? There's not a shred of evidence to support it. Here anthropologist David Graeber presents a stunning reversal of conventional wisdom. He shows that for more than 5,000 years, since the beginning of the agrarian empires, humans have used elaborate credit systems--a system that far preceeded cash or organized barter. It is in this era, Graeber shows, that we also first encounter a society divided into debtors and creditors. With the passage of time, however, virtual credit money was replaced by gold and silver coins--and the system as a whole began to decline. Interest rates spiked and the indebted became slaves. And the system perpetuated itself with tremendously violent consequences, with only the rare intervention of kings and churches keeping the system from spiraling out of control. Debt: The First 5,000 Years is a fascinating chronicle of this little known history--as well as how it has defined human history, and what it means for the credit crisis of the present day and the future of our economy.
On the experience of moral confusion -- The myth of barter -- Primordial debts -- Cruelty and redemption -- A brief treatise on the moral grounds of economic relations -- Games with sex and death -- Honor and degradation, or, on the foundations of contemporary civilization -- Credit versus bullion, and the cycles of history -- The axial age (800 BC - 600 AD) -- The middle ages (600 AD - 1450 AD) -- Age of the great capitalist empires (1450-1971) -- (1971- ).
Includes bibliographical references and index.
Keywords: Debt -- History; Financial crises -- History; Money -- History